Problems in using a comb sample as a stress-free reference for the determination of welding residual stress by diffraction - Ganguly, Supriyo; Edwards, Lyndon; Fitzpatrick, Michael E. (Elsevier, 2010)
Precise measurement of a stress-free reference lattice parameter is vital in the determination of residual stress by diffraction techniques using θ/2θ-based analyses. For the evaluation of the residual strain profile in fusion-welded material, it is particularly important to correct the measured strain point-by-point by a stress-free reference for each spatial location across the weld. This is to take into account the compositional and microstructural variation across the weld caused by the thermal cycle of welding, as local changes in solute content of the parent alloy cause changes in the stress-free lattice parameter. Although ideally such measurements should be obtained from small cubes machined from the weld, the use of a comb sample has previously been proposed as a macro-stress-free reference, with the assumption that each finger of the comb is of insufficient dimension to hold a macro-stress field. This paper presents an approach towards analysis of the stress-free reference values using a comb sample extracted from a variable polarity plasma arc (VPPA) welded plate. It is shown that there is inter-granular stress and retained macro-stress within the comb teeth, and an experimental approach to deal with the problem is proposed.